Health literacy and guideline-adherent lifestyle in people with chronic kidney disease: exploring factors associated with usage intention of a structured m-health program and pilot data on actual behavior change - Schmidt, Laura I.; Jokisch, Mario R.; Espey, Lea; Hentschel, Viet Anh-Thu; Rose, Daniela; Fleig, Susanne; Waldeck, Malte; Best, Jan David; Wagner, Jürgen (Frontiers in Nephrology, 2025)
BackgroundAlthough medical guidelines for chronic kidney disease (CKD) clearly recommend measures such as blood pressure control, dietary changes, regular physical activity, and consistent medication adherence, individuals frequently encounter challenges in implementing these behavioral modifications. In medical practices, there is a lack of time and resources to comprehensively support CKD patients and low-threshold (digital) interventions aimed at enhancing patient activation are needed. This paper analyzes the acceptance and usage intention (Study 1) and the contribution to health literacy and behavioral change (Study 2) of a m-health program for CKD (“Oska”). The Oska program combines personal counseling via video calls with app-based support and is theoretically grounded in the Health Action Process Approach (HAPA), with a strong emphasis on fostering self-efficacy and promoting implementation in daily routines.MethodStudy 1: An online survey was conducted with N = 401 individuals with CKD and/or hypertension, obesity, type 2 diabetes, or coronary heart disease (age: 50–89 years, M = 64.1, 49% female). Participants were recruited via the provider Appinio and presented with a vignette illustrating the Oska program and answered questionnaires on usage intention, desired support, compatible health benefits, health literacy, and perceived usefulness. Study 2: N = 109 participants with CKD, who already took part in the Oska program for an average of 4.7 months (age: 29–84 years, M = 62.3, 64% female, BMI: M = 29.6), completed established questionnaires on working alliance, kidney-specific health literacy, and behavior change. The analysis was conducted using structural equation models and linear regression analyses.ResultsAcceptance and usage intention in study 1 were high and predominantly explained by compatible health benefits, health literacy, and perceived usefulness, but largely independent of sociodemographic factors and health-related variables. In study 2, higher health literacy was primarily fostered by longer program participation and, most notably, by a positive trust relationship (working alliance) (R²adj = .48) Successful behavior change (across all guideline areas) was primarily attributed to a positively evaluated working alliance and Oska’s contribution to health literacy, rather than sociodemographic factors or the number and type of diagnoses (R²adj = .14).DiscussionDigitally delivered coaching combined with app-based support is not only acceptable but may be particularly effective for CKD patients with low health literacy and multiple comorbidities. Relevant determinants include a trusting coaching relationship and a focus on health literacy as well as self-efficacy in implementing measures in everyday life.